Cumulative causation and evolutionary micro-founded technical change: A growth model with integrated economies - Patrick Llerena; André Lorentz (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
We propose to develop in this paper an alternative approach to the New Growth Theory to analyse growth rate divergence among integrated economies. The model presented here considers economic growth as a disequilibrium process. It introduces in a cumulative causation framework, micro-founded process of technical change taking into account elements rooted in evolutionary and Neo-Austrian literature. We then attempt to open the 'Kaldor-Verdoorn law black-box' using a micro-level modelling of industrial dynamics. We use this framework to study the nature and sources of growth rate divergence, focusing on the effect of some macro-economic parameters (income elasticities) and of some technological parameters (technological opportunities and absorptive capacities). If the results remain broadly in Kaldorian lines, this framework allows for more subtle considerations of growth rate divergence.
Keywords: 330; Wachstumstheorie; Evolutionsökonomik; Technischer Fortschritt; Cumulative Causation; Mikroökonomische Fundierung